Risk Behavior and Prevention of Type 2 Diabetes Mellitus in Productive Age Groups in the Work Area of the Tapos Community Health Center UPTD - Nina; Diponegoro, Amanda Putri Dwi Rahmanti; Cahya, Intan Dwi; Al-Hamdy, Mizan Hafidh; Putri, Nazwa Shakila Alisa; Permana, Rafif Dhia; Basoriyah, Taqiyatul (LPPM Universitas Mohammad Husni Thamrin, 2025)
Non-communicable diseases (NCDs) such as stroke, chronic kidney disease, hypertension, and type 2 diabetes mellitus (T2DM) have increased significantly. Type 2 Diabetes Mellitus (T2DM) is a non-communicable disease that has shown a significant increase every year, particularly among the productive age group. Unhealthy lifestyles, lack of physical activity, and low awareness of early detection are the main contributing factors. This study aims to identify risk behaviors and prevention efforts related to T2DM among the productive age population in the working area of UPTD Puskesmas Tapos in 2025. This research employed a descriptive approach through observation, interviews, and literature studies. Primary data were collected through surveys involving 100 respondents of productive age in the Tapos area, while secondary data were obtained from the 2024 Health Profile Report of UPTD Puskesmas Tapos. The results showed that 83.3% of respondents engaged in regular physical activity, but only 62.2% consumed fruits and vegetables consistently. Although 94.4% utilized health services at the public health center, most did not undergo routine health check-ups. Unhealthy eating patterns, insufficient physical activity, and low awareness of routine screening were identified as dominant risk factors. Therefore, continuous health education, promotion of healthy lifestyles, and improved access to screening services are recommended to reduce the prevalence of T2DM among the productive age population.